2017
DOI: 10.1177/1179559x16689676
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use and Risk of Community-Acquired Pneumonia in a Population-Based Cohort Study From North-Eastern Spain

Abstract: Background: Benzodiazepine (Bz) exposure has been identified as a risk factor of community-acquired pneumonia (CAP) in some observational studies, but this remains controversial. This study was designed to quantify the risk of CAP associated with treatment with Bz. Methods: All individuals ⩾14 years of age registered in any of 3 primary health care providers in our area between January 2011 and May 2013 were included in the study. This resulted in a population of 51 912 individuals who contributed to a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Two case‐control studies used the National Health Insurance Research Database of Taiwan; however, we include both two studies in the meta‐analysis because they were conducted by different investigators, and a study conducted by Chen et al provided additional data for individual BZRD drug analysis. Altogether, the meta‐analysis included 12 citations of 10 studies, which involved over 120,000 pneumonia cases from six case‐control studies and four cohort studies . The study selection process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two case‐control studies used the National Health Insurance Research Database of Taiwan; however, we include both two studies in the meta‐analysis because they were conducted by different investigators, and a study conducted by Chen et al provided additional data for individual BZRD drug analysis. Altogether, the meta‐analysis included 12 citations of 10 studies, which involved over 120,000 pneumonia cases from six case‐control studies and four cohort studies . The study selection process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The earliest study was published in 1999 and the most recent in 2018. All included studies were population‐based and were conducted in the USA (n = 2), Europe (n = 7), and Asia (n = 1) . Nine studies identified patients through administrative databases, whereas only one used medical records.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations